Cannabis, Decision‐Making, and Online Assistance Seeking. Issue 6 (18th September 2019) - Evans, Mark; Ogeil, Rowan P.; Phillips, James G.
Abstract : Background and Objectives: Maladaptive decision‐making strategies could contribute to cannabis‐related problems, as some individuals may neither select safe patterns of cannabis use, nor seek treatment. Methods: To explore decision‐making styles and their relationship to cannabis‐related harm, 153 respondents completed the Cannabis Use Disorders Identification Test‐Revised (CUDIT‐R), the Melbourne Decision Making Questionnaire (MDMQ), and answered questions about their willingness to seek online: (1) further information or (2) treatment for cannabis‐related issues. Results: Multiple regression considered relationships between problematic cannabis use, decision‐making style, and cannabis use within the past month. Subscales of the CUDIT‐R revealed that: (1) hazardous use was associated with higher hypervigilance and higher decisional self‐esteem; (2) dependence symptoms were associated with lower vigilance and higher procrastination; and (3) harmful use was associated with higher procrastination. People with symptoms of CUD were less likely to seek further help or support online if prone to procrastination or buckpasssing. Discussion and Conclusions: Decisional style influenced cannabis use and symptoms. Those people with cannabis‐related problems that did not seek online assistance were defensively avoidant. Scientific Significance: Procrastination is a feature of problematic cannabis use. Online offers of assistance may be ignored by defensively avoidant CUD clients. (Am J Addict 2019;00:1–7)